CREATION OF THE MULTIMEDIA ELECTRONIC INFORMATION ON EDUCATIONAL RESOURCES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper discusses technologies for creating multimedia electronic information, educationalresources for educational institutions.